Divergent preS Sequences in Virion-Associated Hepatitis B Virus Genomes and Subviral HBV Surface Antigen Particles From HBV e Antigen-Negative Patients. (8th March 2018) - Peiffer, Kai-Henrik; Kuhnhenn, Lisa; Jiang, Bingfu; Mondorf, Antonia; Vermehren, Johannes; Knop, Viola; Susser, Simone; Walter, Dirk; Dietz, Julia; Carra, Gert; Finkelmeier, Fabian; Zeuzem, Stefan; et al.
Abstract : PreS mutations, detected in released viral genomes, did not affect HBsAg expression in HBeAg-negative chronic HBV-infected patients. In these patients, HBsAg is presumably derived from the integrated DNA. This HBsAg source should be considered for novel antiviral strategies. Abstract: Background: Hepatitis B virus (HBV) surface proteins (HBsAg) coat the viral particle and form subviral particles (SVPs). Loss of HBsAg represents a functional cure and is an important treatment goal. Methods: We analyzed the impact of the HBV genotypes A–E and pre-S mutations on SVP expression in hepatitis B virus e antigen (HBeAg)-negative chronic HBV-infected patients. A HBV genome harboring a preS1-deletion was analyzed in hepatoma cells. Results: We observed a genotype-specific ratio of the 3 surface proteins (SHBs/MHBs/LHBs), reflecting differences in the morphology and composition of SVPs. Deletions/mutations in the preS1/preS2 domain, detected in released viral genomes, did not affect the molecular weight of MHBs and LHBs in these patients. In contrast, LHB molecular weight was altered in vitro using an HBV genome harboring a preS1-deletion derived from one of these patients. Conclusion: Differences in composition of SVPs may result in genotype-specific immunogenicity and pathogenesis. In the patients with preS-mutations, secreted HBsAg and released viral genomes cannot be derived from the same genetic source. As viral genomes are derived from covalently closed circular DNA (cccDNA), HBsAg is presumably derived from integrated DNA. This important HBsAg source should be considered for novel antiviral strategies in HBeAg-negative chronic HBV-infected patients.